Will the presumption of the existence of an employment relationship lead to persons performing work through digital labour platforms being afforded the full set of employment rights? Considerations under the EU Directive on improving working conditions in platform work - Woźniak, Daria (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
Labour law has been undergoing dynamic changes in recent years, linked among other things to the development of artificial intelligence or digitalization. New, previously unknown, forms of labour provision are emerging. One of these is work through online platforms. To adapt to the changes taking place in society, a Directive of the European Parliament and of the Council (EU) on the improvement of working conditions through platforms was adopted on 23 October 2024. Member States have until 2 December 2026 to implement this directive. The purpose of this chapter is to identify the rights gained under it by persons providing work via platforms and to determine whether the rights of these persons will indeed be equalised with those of employees regulated by the Polish Labour Code.